Robot Arm Teleoperative System Design with Flex Sensor - Alfianto, Imam; Falih, Andi; Halim, Abdul (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
With the technology currently available, the hands of the most advanced humanoid robots used in prosthetics or robotics can be very expensive, making them inaccessible to disabled and robotics enthusiasts. Using 3D printing technology, these robotic hands can be mass produced and have the basic functions of a sophisticated and inexpensive expensive hand. The hand robot is controlled using sensor gloves that can read the finger movements and the compressive power of the user’s fingers. The flex sensor is a sensor that has a function to detect curvature. The reason I use the flex sensor is because of a need to get motion values ??for the curvature of the fingers. This research consists of selecting a 3D printed hand model, assembling the mechanical and electronic components of the robot arm, making software, testing the robot arm and integrating it with sensors and implementing tele-operations. The robot hand is able to hold 358 grams of load, with an efficiency of only 5.98% compared to the torque output of the actuator. The maximum error for sensor reading is 5.61% and integration is 11.73%.